Genotype by Seeding Rate Interaction in Wheat - A. J. Azevedo; S. Varela; R. Lollato; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2017)
Genotype by seeding rate interaction can play a critical role in understanding wheat (Triticum aestivumL.) yield potential. The objective of this study was to quantify wheat yield response to seeding rates by contrasting genotypes (high- vs. low-tillering). One study was planted at two locations: Ashland Bottoms (dryland and conventional tillage) and at Topeka (irrigated and no-tillage) field research stations (Kansas). The two winter wheat varieties were sown at four different seeding rates (40, 80, 120, and 160 lb/a). Measurements consisted of stand counts, canopy coverage (estimated via imagery collection), determination of early-season gaps in the final stand (missing plants), spacing between plants, and imagery collection via small-unmanned aerial vehicle systems (sUAVS). For the first year, average yield was greater at Ashland Bottoms (79.8 bushels per acre) than at Topeka (50.4 bushels per acre). Statistically, neither seeding rate, variety, nor their interaction resulted in significant differences at Topeka. Seeding rate significantly affected yields at Ashland Bottoms, with positive yield response as seeding rate increased but plateauing at 120 lb/a. Further research is in place to test the genotype and seeding rate interactions for providing a better understanding of the complexity behind the influence of these factors on wheat yields.
Keywords: wheat; seeding rate; genotype; small-unmanned aerial vehicle systems; imagery